2019
DOI: 10.1039/c8cc09372e
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable lithium plating by a multifunctional electrolyte additive in a lithium-sulfurized polyacrylonitrile battery

Abstract: The formation of lithium dendrites is recognized as the worst problem for lithium metal batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…LKNO||LKNO and Li||Li symmetric cells were then assembled and cycled at 1 mA cm −2 and 1 mA h cm −2 (Figure 4C). Supported by the enhanced charge transfer kinetics through the interface, the LKNO electrode showed flat and smooth voltage profiles with low overpotential (~0.06 V after 400 h) in sharp contrast to ~0.18 V of pure Li electrode after 300 h. The sustained release of KNO 3 from LKNO into electrolyte ensured dynamic repairing of SEI by NO 3 − and dense Li plating due to the electrostatic shield of K + during long‐term cycling 26,31,32 . As a comparison, a fast increase of voltage polarization occurred for pure Li electrode.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…LKNO||LKNO and Li||Li symmetric cells were then assembled and cycled at 1 mA cm −2 and 1 mA h cm −2 (Figure 4C). Supported by the enhanced charge transfer kinetics through the interface, the LKNO electrode showed flat and smooth voltage profiles with low overpotential (~0.06 V after 400 h) in sharp contrast to ~0.18 V of pure Li electrode after 300 h. The sustained release of KNO 3 from LKNO into electrolyte ensured dynamic repairing of SEI by NO 3 − and dense Li plating due to the electrostatic shield of K + during long‐term cycling 26,31,32 . As a comparison, a fast increase of voltage polarization occurred for pure Li electrode.…”
Section: Resultsmentioning
confidence: 93%
“…Experimental results revealed that KNO 3 in the LKNO composite could be released into the electrolyte and remained as a stable component on cycling, which could dynamically repair the SEI and stabilize the Li metal electrode on cycling. Importantly, K + from KNO 3 could adsorb on the protrusions of the electrode to form an electrostatic shield and suppress the dendritic growth 31,32 . With these advantages, stable cycling in both LKNO||LKNO symmetric cells and LKNO||LiNi 0.6 Mn 0.2 Co 0.2 O 2 (LKNO||NCM) full cells with high cathode loading (~15 mg cm –2 ) were realized.…”
Section: Introductionmentioning
confidence: 99%
“…It is favorable to form the Li nucleus rapidly, rather than large Li dendrites. [ 6 ] Generally, electrolyte additives can contribute to the formation of robust SEI film by increasing the content of some inorganic component with high ionic conductivity and low electronic conductivity, for example, LiF and Li x S n ( n > 4) , [ 26–28 ] which have been demonstrated to contribute the formation of high‐quality SEI for enhancing the performance of LMBs. Li 3 P, as one of the fast Li + conductors (≈10 −4 S cm −1 at ambient temperature), is an ideal inorganic component of SEI film, [ 29 ] which has been proved by Qian and Goodenough's groups, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed to enhance the quality of SEI film via adopting electrolyte additives to stabilize it [5][6][7][8][9] or constructing artificial SEI film on the surface of Li metal to inhibit the growth of Li dendrites and realize uniform deposition of Li metal [10][11][12][13][14]. Frankly speaking, the modified SEI cannot guarantee a perfect cycling performance, because the huge volume fluctuation of the Li anode in the process of charging/ discharging has not been solved [15].…”
Section: Introductionmentioning
confidence: 99%